Reply to Comment on “Comparison of Cloud Cover Detection Algorithms on Sentinel–2 Images of the Amazon Tropical Forest” - Alber Hamersson Sanchez; Michelle Cristina A. Picoli; Gilberto Camara; Pedro R. Andrade; Michel Eustaquio D. Chaves; Sarah Lechler; Anderson R. Soares; Rennan F. B. Marujo; Rolf Ezequiel O. Simões; Karine R. Ferreira; Gilberto R. Queiroz (Remote Sensing, 2021)
In their comments about our paper, the authors remark on two issues regarding our results relating to the MACCS-ATCOR Joint Algorithm (MAJA). The first relates to the sub-optimal performance of this algorithm under the conditions of our tests, while the second corresponds to an error in our interpretation of MAJA’s bit mask. To answer the first issue, we acknowledge MAJA’s capacity to improve its performance as the number of images increases with time. However, in our paper, we used the images we had available at the time we wrote our paper. Regarding the second issue, we misread the MAJA’s bit mask and mistakenly labelled shadows as clouds. We regret our error and here we present the updated tables and images. We corrected our estimation and, consequently, there is an increment in MAJA’s accuracy in the detection of clouds and cloud shadows. However, these increments are not enough to change the conclusion of our original paper.